1997
DOI: 10.5694/j.1326-5377.1997.tb140041.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B and C in New South Wales prisons: prevalence and risk factors

Abstract: Objectives: To determine the prevalence of hepatitis B virus (HBV) and hepatitis C virus (HCV) infection among inmates entering the New South Wales correctional system and to examine risk factors for infection. Design: Cross‐sectional survey. Setting: Reception Centre at Long Bay Correctional Centre, Sydney, New South Wales, June to December 1994. Participants: 408 adult male inmates received at the Reception Centre (28% of the 1450 new inmates eligible for compulsory HIV testing). Outcome measures: Presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
85
1
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(105 citation statements)
references
References 14 publications
17
85
1
2
Order By: Relevance
“…Although significantly lower than the 23% prevalence reported in a Victorian study of juvenile detainees, 6 the prevalence in the small number of NSW females was similar 3 (18%), and both figures are significantly higher than the 2% prevalence reported in US juvenile detainees. 17 However, these juvenile rates are considerably lower than the almost 40% prevalence of hepatitis C antibody reported in studies of Australian adult prisoners 35,36 highlighting the window of opportunity for risk-reduction education in young detainees.…”
Section: Hepatitis C Prevalencementioning
confidence: 95%
“…Although significantly lower than the 23% prevalence reported in a Victorian study of juvenile detainees, 6 the prevalence in the small number of NSW females was similar 3 (18%), and both figures are significantly higher than the 2% prevalence reported in US juvenile detainees. 17 However, these juvenile rates are considerably lower than the almost 40% prevalence of hepatitis C antibody reported in studies of Australian adult prisoners 35,36 highlighting the window of opportunity for risk-reduction education in young detainees.…”
Section: Hepatitis C Prevalencementioning
confidence: 95%
“…Many studies in Australia and overseas have reported a high prevalence of BBVs amongst prisoners [5][6][7]. The seroprevalence of HCV in Victorian prisons in 1991/1992 was 39 % [8] and elsewhere in Australia in 1994 was 36% [9]. The seroprevalence of HCV in prisoners who had injected in prison in that study was over 60 % [10].…”
Section: Introductionmentioning
confidence: 96%
“…Among those who reported injecting drug use, 66% are HCV positive. 12,13 However, there is limited information on HRQOL among prisoners. Very little is known about potential HRQOL impairment related to HCV.…”
Section: Introductionmentioning
confidence: 99%